Hadith, Law, And Orientalism: A Critical Study of Joseph Schacht’s Theoretical Contributions - Mowafg Abrahem Masuwd (PT. Global Pustaka Ilmiah, 2025)
This study aims to examine classical and orientalist approaches to Islamic law, with a focus on the development and influence of Joseph Schacht’s theories. It explores Schacht’s understanding of the origins of Islamic jurisprudence, especially hadith, and their impact on Islamic law. This is a qualitative study based on library research. The results of this research show that Schacht uses a socio-historical approach to understanding Islamic law, emphasizing that the development of Islamic law is greatly influenced by the social and cultural context. Schacht argues that many hadith were codified in the early second century of the Hijra and that many of them were the result of reconstructions that emerged as a result of debates among early Islamic legal schools. This opinion has been challenged by various Muslim academics who are trying to prove that hadith have been written and transmitted since the time of the Prophet, both orally and in writing. Therefore, further research that focuses on analyzing hadith manuscripts that have not been translated is needed to provide a deeper understanding of the process of recording hadith and the development of Islamic law.